Pendekatan Antrhopometry Tinggi Penglihatan Mata Sebagai Dasar Ukuran Redesain Median Jalan (Studi Kasus Jalan Diponegoro Simpang Gili Tugel) - Mushoffan, Ali; Hidayati, Tri Susila (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2018)
The road median is a physical separation of the traffic lane that serves to eliminate traffic conflictsfrom the opposite direction, which in turn will improve the safety of traffic. road infrastructure factorsthat do not meet safety standards. An example is due to the manufacture of a median road at eachintersection that does not meet such standards as too wide and too high such as in the tegal city ofDiponegoro, this indicates reduced main function of the median road, Antrhopometry is anapproximation of the size of the human body. In this study discusses how to make the mediandesign does not eliminate the main function of traffic separator traffic by using antrhopometry. Thedata used are high-dimensional data of sight and median dimension size, looking forstandardeviation as the lowest value of high vision value to find the right value as a redesignracetrack.